RIGHT OF CITIZENS OF THE REPUBLIC OF KAZAKHSTANTO PARTICIPATE IN REFERENDUM (Journal of actual problems of jurisprudence, 2019)
The author of the article considers the rights of the citizens of Kazakhstan to participation in referendum. Also the differentdefinitions of the concept of referendum and the stages of its democratic formation are considered in this article.